The dimensional accuracy of polyvinyl siloxane impression materials using two different impression techniques: An in vitro study - Nirmala Kumari; D B Nandeeshwar (Wolters Kluwer Medknow Publications, 2015)
Aim of the Study: To evaluate and compare the linear dimensional changes of the three representative polyvinyl siloxane (PVS) impression materials and to compare the accuracy of single mix with double mix impression technique. Methodology: A study mold was prepared according to revised American Dental Association specification number 19 for nonaqueous elastic dental impression materials. Three PVS impression materials selected were Elite-HD, Imprint™ II Garant, Aquasil Ultra Heavy. Two impression techniques used were single mix and double mix impression technique. A total of 60 specimens were made and after 24 h the specimens were measured using profile projector. Statistical Analysis: The data were analyzed using one-way analyses of variance analysis and significant differences were separated using Student's Newman-Keul's test. Results: When all the three study group impression materials were compared for double mix technique, the statistically significant difference was found only between Imprint™ II Garantand Elite-HD (P < 0.05). Similarly, using single mix technique, statistically significant difference were found between Elite-HD and Imprint™ II Garant (P < 0.05) and also between Aquasil Ultra Heavy and Elite-HD (P < 0.05). When the linear dimensional accuracy of all three impression material in double mix impression technique and single mix impression technique were compared with the control group, Imprint™ II Garant showed the values more nearing to the values of master die, followed by Aquasil Ultra Heavy and Elite-HD respectively. Conclusion: Among the impression materials Imprint™ II Garant showed least dimensional change. Among the impression techniques, double mix impression technique showed the better results.